Collective Bargaining and Academic Freedom : Are they Compatible? - Woods, H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
In this paper, the author supports the idea that collective bargaining presents some real dangers to academic freedom on the campuses of Canadian Universities.